Long Noncoding RNA MIR4435-2HG is Involved in Osteogenic Differentiation and Inflammation in Human Dental Pulp Stem Cells - Feijun Wu; Zhisheng Jiang (International Dental Journal)
Introduction and aims: Pulpitis is a common oral pathology, necessitating an investigation into its pathogenesis and therapeutic targets. The aim of this study was to elucidate the function of long noncoding RNA MIR4435-2 host gene (MIR4435-2HG) in osteogenic differentiation and inflammatory response of dental pulp cells in vitro, offering insights into pulpitis mechanisms and potential treatment strategies. Methods: The expression of MIR4435-2HG was quantified by real-time quantitative PCR in pulp samples. Human dental pulp stem cells (hDPSCs) were utilized to investigate the impact of MIR4435-2HG on osteogenic differentiation. Inflammatory responses were induced by treating hDPSCs with lipopolysaccharide (LPS). The viability and apoptosis of hDPSCs were determined using Cell Counting Kit-8 and Apoptosis assays, respectively. The targeting relationship between MIR4435-2HG and miR-296-5p was substantiated using Dual-Luciferase reporter gene assay. Results: MIR4435-2HG was upregulated in the inflamed pulp tissues and exhibited favourable efficacy in differentiating between healthy and inflamed pulp. In osteogenesis-induced hDPSCs, MIR4435-2HG suppressed alkaline phosphatase activity and the expression of osteogenic markers (dentin matrix protein-1 and dentin salivary phosphoprotein). In LPS-stimulated hDPSCs, knockdown of MIR4435-2HG decreased the mRNA levels of inflammatory mediators (TNF-α, IL-1β, and IL-6), promoted cell proliferation, and repressed apoptosis. miR-296-5p was negatively modulated by MIR4435-2HG, and downregulation of miR-296-5p counteracted the effects of MIR4435-2HG knockdown on inflammation and cellular phenotype. Conclusion: The present investigation indicates that MIR4435-2HG suppresses osteogenic differentiation while facilitating LPS-triggered inflammation in hDPSCs through miR-296-5p modulation. Clinical relevance: This study investigated how MIR4435-2HG regulates osteogenic differentiation in hDPSCs and modulates LPS-induced inflammatory reactions. The findings shed light on its possible involvement in pulpitis pathogenesis and suggest its therapeutic potential for dental tissue repair.